Ocular biometry and determinants of refractive error in rural Myanmar: the Meiktila Eye Study. Issue 12 (16th October 2008) - Warrier, S; Wu, H M; Newland, H S; Muecke, J; Selva, D; Aung, T; Casson, R J
Abstract : Objective: To describe the ocular biometry and determinants of refractive error in an adult population in Myanmar. Methods: A cross-sectional, population-based survey of the inhabitants 40 years of age and over from villages in the Meiktila District was performed; 2481 eligible participants were identified, and 2076 participated in the study. Biometric components including axial length (AL), anterior chamber depth (ACD), vitreous chamber depth (VCD), lens thickness (LT) and corneal curvature (CC) were measured. Lens opalescence was measured using the Lens Opacity Grading System III. Non-cycloplegic refraction was measured with an autorefractor. Results: Complete biometric, refractive and lenticular data were available on 1498 participants. Men had longer ALs, ACDs, VCDs and steeper CCs than women. There was an increase in LT, nuclear opalescence (NO) and myopic shift with increasing age, with no significant change in AL with age. In the 40–59 year age group, VCD was a significant predictor of refractive error, but LT (p<0.001) and NO (p<0.001) were stronger predictors. In the 60+ age group, NO (p<0.001) was also the dominant predictor of refractive error. Conclusion: This Burmese population, particularly women, has a relatively short AL and ACD. NO is the strongest predictor of refractive error across all age groups in this population.